Performance Insights of Puskesmas Tilango through the Balanced Scorecard Approach - Walangadi, Zulkifli (Jurnal Ners, 2024)
This study aimed to assess the performance of the Puskesmas Tilango's inpatient unit using the Balanced Scorecard (BSC) approach, introduced by Kaplan and Norton in 1992. The performance was viewed from four perspectives: customer, internal business process, financial, and learning and growth. Results revealed that patient satisfaction was satisfactory, yet market share was not ideal. Despite no health service innovations being implemented, financial indicators such as revenue and expenditure decreased, but the Cost Recovery Rate (CRR) was satisfactory. Concerning learning and growth, while employee learning rate was commendable, satisfaction, turnover rate, and productivity were unsatisfactory. Based on these findings, it was evident that the overall performance of Puskesmas Tilango's inpatient unit was lacking. Recommendations propose the adoption of the BSC for future performance evaluations, enhancement of facilities in line with the increasing population, and emphasis on employee welfare to improve performance. This study provides valuable insights for health administrators and policymakers, emphasizing the need for continuous assessment and improvement in health centers.